2022
DOI: 10.1002/jmv.27874
|View full text |Cite
|
Sign up to set email alerts
|

Disease of influenza virus and SARS‐CoV‐2 coinfection: Flurona or Flucovid?

Abstract: To the Editor, Recently, the new term Flurona has emerged to describe coinfection of influenza virus and SARS-CoV-2, causing flu, and COVID-19, respectively. 1 This terminology, however, seems to suggest a recombinant virus with genes from both influenza virus and coronavirus, like Delmicron with gene fragments from SARS-CoV-2 variants Delta and Omicron. Indeed, Delmicron and Flurona were listed in parallel in the titles of some publications, and Flurona was hinted as "a new variant" in the header of some news… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Many case reports show that, compared with a single virus infection, coinfection with SARS‐CoV‐2 and FluA leads to a rapid development of more serious clinical symptoms. 4 In fact, in vivo experiments have shown that FluA infection increases the susceptibility of cells to SARS‐CoV‐2 infection. 5 Thus, rapid and sensitive differentiation between SARS‐CoV‐2 and FluA infections has important implications for the management and treatment of patients with influenza‐like illness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many case reports show that, compared with a single virus infection, coinfection with SARS‐CoV‐2 and FluA leads to a rapid development of more serious clinical symptoms. 4 In fact, in vivo experiments have shown that FluA infection increases the susceptibility of cells to SARS‐CoV‐2 infection. 5 Thus, rapid and sensitive differentiation between SARS‐CoV‐2 and FluA infections has important implications for the management and treatment of patients with influenza‐like illness.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the overlapping seasons of the SARS‐CoV‐2 pandemic and FluA epidemic may expose a large number of people to an increased risk of simultaneous infection with both viruses. Many case reports show that, compared with a single virus infection, coinfection with SARS‐CoV‐2 and FluA leads to a rapid development of more serious clinical symptoms 4 . In fact, in vivo experiments have shown that FluA infection increases the susceptibility of cells to SARS‐CoV‐2 infection 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that IAV infection enhanced SARS-CoV-2 infection by promoting ACE2 expression. 33 , 51 , 52 However, the effects of SARS-CoV-2 on IAV infection remain unknown. Here, we showed that N promoted IAV replication but was repressed by MCL-1 knock-down or S63845 administration.…”
Section: Discussionmentioning
confidence: 99%
“…What's more serious is that the mixed infection of SARS‐CoV‐2 and influenza A or B has caused great trouble to clinical diagnosis and treatment. The susceptibility of COVID‐19 in influenza‐infected people is enhanced, and the condition of mixed infection of COVID‐19 is aggravated, which is easy to develop into severe pneumonia in the present work 28,29 . We developed a more convenient and faster method for detecting SARS‐CoV‐2, H1N1, H3N2, and influenza B based on recombinase polymerase amplification (RPA) technology.…”
Section: Introductionmentioning
confidence: 93%
“…The susceptibility of COVID‐19 in influenza‐infected people is enhanced, and the condition of mixed infection of COVID‐19 is aggravated, which is easy to develop into severe pneumonia in the present work. 28 , 29 We developed a more convenient and faster method for detecting SARS‐CoV‐2, H1N1, H3N2, and influenza B based on recombinase polymerase amplification (RPA) technology. In our study, N, E and ORF1ab genes of SARS‐CoV‐2 and genes encoding the matrix protein (M) for H1N1, and the hemagglutinin (HA) for H3N2, and the polymerase A (PA) for Influenza B were selected and specific primers were designed.…”
Section: Introductionmentioning
confidence: 99%